Major effect of transcytosis on nano drug delivery to pancreatic cancer - Xiangsheng Liu; Jinhong Jiang; Andre E. Nel; Huan Meng (Molecular & Cellular Oncology, 2017)
We demonstrated that activated transcytosis is a major mechanism to complement the classic enhanced permeability and retention effect in pancreatic cancer. This was achieved by using an iRGD peptide that triggers transcytosis pathway at the tumor site. Co-administration of unconjugated iRGD substantially improved the effect of the chemotherapeutics delivering nanocarrier, and resulted in survival improvement in mice. Since the iRGD effect is commensurate with neuropilin-1 expression on tumor vasculature, it is necessary to contemplate a personalized approach to implement this technology.